The biology and behavior of the longhorned beetle, Dectes texanus on sunflower and soybean - Michaud, J. P.; Grant, Angela K. (My University, 2008)
The biology and behavior of the longhorned beetle Dectes texanus LeConte (Coleoptera: Cerambycidae) was studied on two host plants that suffer economic losses from this pest; sunflower, Helianthus annuus, and soybean, Glycines max. Reciprocal crosses of D. texanus collected from the two plants all produced viable progeny, indicating that conspecific insects attack both crops. Pupae from soybean stalks weighed about 40% less than those from sunflower, and adults fed on soybean lived a mean of 23 days, compared to a mean of 53 days (males) and 76 days (females) for those fed sunflower. A female's larval host plant had no effect on her tendency to ovipuncture plants of either type in a greenhouse trial. A field-tested population collected exclusively from sunflower contained three types of females in similar proportions: those that laid eggs only on sunflower, those that laid only on soybean, and those that laid equally on both host plants. Females in field trials fed more on the plant they had fed on in the laboratory, but soybean-fed females fed more on soybean than did sunflower-fed females. Females fed soybean also made more ovipunctures on soybean plants in field trials than sunflower-fed females, but their responses to sunflower plants were similar. Females displayed higher total ovipositional activity when they encountered sunflower first in the field, and lower total activity when they encountered soybean first. Feeding scores were significantly correlated with ovipunctures and eggs on both plant types. We conclude that sunflower is the preferred host plant, although females will accept soybean when it is the only available food. The results suggest that D. texanus is still in the initial stages of a host range expansion with female host selection behavior demonstrating both genetic influences and phenotypic flexibility. Sunflower represents a nutritionally superior, ancestral host plant and relatively high fitness costs are still associated with utilization of the novel host plant, soybean, costs that may be offset by benefits such as reduced intraspecific competition. These potential benefits and their consequent implications for D. texanus host range evolution are hypothesized and discussed.
Citation: Michaud JP, Grant AK. 2005. The biology and behavior of the longhorned beetle, Dectes texanus on sunflower and soybean. 15pp. Journal of Insect Science 5:25, available online: insectscience.org/5.25
Keywords: Evolution; Fitness; Glycines max; Helianthus annuus; Host range; Longevity; Oviposition; Polyphagy; Reproduction